Pengaruh Rasio Keuangan Terhadap Financial Distress Pada Masa Pandemi Covid-19 Tahun 2018 – 2021 - Siti Aminah; Sri Handayani (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
This study aims to analyze the effect of liquidity ratios, leverage ratios, profitability ratios, and activity ratios on financial distress in the restaurant, hotel & tourism sub-sector service industry listed on the Indonesia Stock Exchange during the Covid-19 pandemic in 2018-2021. The liquidity ratio is measured by using the current ratio. The leverage ratio is measured using the debt to asset ratio. The profitability ratio is measured by using the net profit margin. The activity ratio is measured by using total assets turnover. Financial distress is measured using the Springate model. The sample used in this study were 35 restaurants, hotels & tourism sub-sector companies listed on the Indonesia Stock Exchange with a total of 88 data. The data used is quantitative data sourced from secondary data in the form of financial report publications. The data analysis method used is a descriptive statistical method and multiple linear regression analysis method. The results of this study indicate that the liquidity ratio, leverage ratio, profitability ratio, and activity ratio simultaneously affect financial distress. Liquidity ratio partially has no effect on financial distress. Leverage ratio partially has no effect on financial distress. Profitability ratio partially has no effect on financial distress. Activity ratio partially has a positive effect on financial distress.